Methodological basis imposing restrictions in land use, burdened land rights during land tenure - Dorosh, Y. (Land Management, Cadastre and Land Monitoring, 2017)
The question of balanced consolidation of social legislation in a reasonable ratio of land rights and the interests of society as a whole, as well as local communities, citizens and legal entities established by them are general in nature and require specificity it is. Proved that one way of solving this problem is the establishment of restoictions of land rights, restrictions in land use. However, the mechanism of regulation establishment, implementation and termination of restrictions on the rights to land are not very functional and needs improvement. Current legislation in Ukraine does not contain a balanced set of regulations that would determine the nature and objectives of the restrictions, including encumbrances of land rights, their types, the reasons establishing and implementing restrictions of ownership and other rights to land and so on. Based on our analysis, we provide scientifically grounded suggestions on improving the legal framework, particularly, in terms of restrictions on land use and registration in the land management process, as an important means of influence on those rights in order to ensure rational land use and protection it is. Proved that the efficiency of administrative decisions during setting restrictions on land use purpose and usage of land is possible on the basis of land zoning, thus, it is necessary to adopt the Law of Ukraine "On land zoning." In addition, the current classification of land use restrictions, which was proposed by prominent scientists in Ukraine AM Tretyak (classification of restrictions in land use by functional features), and D.S. Dobryak and D.I. Babmindra (classification of restrictions on land use based on their placement by owners and land users), is complemented by types, namely: legal, environmental, ecological, technological, sanitation, urban and special. In the result of scientific studies,we have proposed a model of methodological process of land management actions on formation of territorial restrictions in land use, formed on the principles of state security, a combination of state and local interests, to achieve a balanced ratio of economic and environmental interests of society and to ensure rational land use. Information on restrictions on land use rights and encumbrances on the land, was amended land systematized: • formation of land use and protection zones of objects and territories nature reserve fund objects Environmental Network; • definition (specification) of borders of natural and agricultural zoning and parcels with especially valuable land; • definition (specification) of land borders and security zones and areas of historical, cultural, health and recreational purposes; • definition (specification) of land borders and security zones, objects (industry, transport, communications, defense, etc.) and their protection zones; • definition (specification) of limits of water protection zones and coastal strips, objects of sanitary protection; • definition (specification) of limits of radioactive contaminated territories, and contaminated by heavy metals; • definition (specification) limits encumbrances established easements, contracts, court order; • definition (specification) limits areas formed in accordance with the previously approved land management documentation; • definition (specification) boundaries of territories with special regime of land use; • definition (approval) of the legal regime of land use in areas of special protection of land and formation of restrictions and encumbrances in land use. Keywords: legal regulation, burdening land rights, restrictions in land use, land management, classification methodology.